Otimização da produção e extração de metabólitos com atividade antioxidantes a partir do fungo Botryosphaeria dothidea isolado do bioma Pampa - Valente, Isabela de Lourdes (2017)
In this work the ultrasound was used to increase the production of metabolites with antioxidant activity obtained from the submerged fermentation of the fungus Botryosphaeria dothidea, followed by different extraction methods: with soxhlet, extraction with supercritical fluid with CO2 solvent and compressed LPG of the biomass of the microorganism. Ultrasound treatment was applied through a Rotational Central Compound Design (DCCR) with different sonication times (1 to 15 min), at different stages of the fermentation process, under various stirring rates (0 to 150 rpm). Dependent variables to the antioxidant activity of the hydroxyl radical and DPPH (2,2-diphenyl-1-picrylhydrazyl) analyzed in the fermented broth (supernatant). For the hydroxyl radical, although the model did not have a significant adjustment to 5 %, there was an increase in antioxidant activity compared to the control, without sonication, in 70 % of the experiments and with values up to 7 % higher. Rotation was the only significant parameter at 5 % in DPPH analysis. In order to analyze the antioxidant capacity of the biomass resulting from the fermentation processes, extractions were carried out at different temperatures and pressures with the supercritical CO2 (40, 50 and 60 º C and 150, 200 and 250 bar) and compressed LPG (20, 30 and 40 ° C and 15, 25 and 35 bar). The highest yield, 1.14 %, was determined by the CO2 of the supercritical fluid using ethanol as co-solvent, followed by 0.94 % with the solvent LPG and 0.86 % with the solvent CO2. Bioactive compounds with antioxidant activity were found in the extractions with supercritical CO2 and Soxhlet solvent using ethanol and ethyl acetate as solvents, identifying 1,4-diaza-2,5-dioxobicyclo [4.3.0] nanone.